No limit? The multiphasic uptake of silicic acid by benthic diatoms - Aude Leynaert; Sorcha Ní Longphuirt; Pascal Claquin; Laurent Chauvaud; Olivier Ragueneau (Limnology and Oceanography, 2009)
Silicic‐acid uptake kinetics for a field population of benthic diatoms were examined using a radioisotope tracer over a concentration range of 0‐300 µmol L ‐1 . The microphytobenthos half saturation constant (54 µmol L ‐1 ) and specific uptake rates (0.096 h ‐1 ) for silicic acid were well above those usually found in the pelagic environment. Silicic‐acid kinetics were hyperbolic only at low concentrations (≪60 µmol L ‐1 ). At higher concentrations, a second mechanism that did not suggest saturation was activated. Many benthic diatoms are motile and migrate vertically in the upper few centimeters of sediment where there are strong gradients of nutrient concentrations. The multiphasic uptake may allow them to take maximum advantage of the high silicic‐acid concentrations found at depth.